Opportunities for increasing CO2 storage in deep, saline formations by active reservoir management and treatment of extracted formation water: Case study at the GreenGen IGCC facility, Tianjin, PR China. (November 2016) - Ziemkiewicz, Paul; Stauffer, Philip H.; Sullivan-Graham, Jeri; Chu, Shaoping P.; Bourcier, William L.; Buscheck, Thomas A.; Carr, Timothy; Donovan, Joseph; Jiao, Zunsheng; Lin, Lianshin; Song, Liaosha; Wagoner, Jeffrey L.
Highlights: Extraction of water during CO2 storage will control pressures and reduce caprock failure risks. Pressure drawdown profiles can be used to proactively plan storage capacity. The case study location has low-salinity water that is an excellent for treatment and use. Abstract: Carbon capture, utilization and storage (CCUS) seeks beneficial applications for CO2 recovered from fossil fuel combustion. This study evaluated the potential for removing formation water to create additional storage capacity for CO2, while simultaneously treating the produced water for beneficial use. The process would control pressures within the target formation, lessen the risk of caprock failure, and better control the movement of CO2 within that formation. The project plans to highlight the method of using individual wells to produce formation water prior to injecting CO2 as an efficient means of managing reservoir pressure. Because the pressure drawdown resulting from pre-injection formation water production will inversely correlate with pressure buildup resulting from CO2 injection, it can be proactively used to estimate CO2 storage capacity and to plan well-field operations. The project studied the GreenGen site in Tianjin, China where Huaneng Corporation is capturing CO2 at a coal fired IGCC power plant. Known as the Tianjin Enhanced Water Recovery (EWR) project, local rock units were evaluated for CO2 storage potential and produced water treatment options were then developed. Average treatment cost for produced water with a cooling water treatment goal ranged from 2.27 to 2.96 US/m 3 (recovery 95.25%), and for a boiler water treatment goal ranged from 2.37 to 3.18 US/m 3 (recovery 92.78%). Importance analysis indicated that water quality parameters and transportation are significant cost factors as the injection-extraction system is managed over time. The study found that in a broad sense, active reservoir management in the context of CCUS/EWR is technically feasible. In addition, criteria for evaluating suitable vs. unsuitable reservoir properties, reservoir storage (caprock) integrity, a recommended injection/withdrawal strategy and cost estimates for water treatment and reservoir management are proposed.